Customer purchase intention towards Takaful Insurance of Perbadanan Melaka Holdings Sdn. Bhd. (PMH) / Shahrizal Shamsuddin and Mat Faris Mohd Taib - Shamsuddin, Shahrizal; Mohd Taib, Mat Faris (Arshad Ayub Graduate Business School, 2018)
Takaful is an insurance scheme that is Shariah compliant. Globally, the Takaful industry has been growing rapidly, appealing to both Muslims and non-Muslims. The industry is expected to grow by 15-20% annually with contributions expected to reach USD20 billion by 2017. However, the penetration rate for Takaful Insurance in Malaysia remained small, which indicates a significant opportunity for future growth. This study is aimed at investigating the factors influencing the Islamic insurance purchasing intention among Malaysian. Challenges that are facing the takaful industry in Malaysia ranging from competitive elements, customers knowledge, demand for better products choice, perception of customers, services quality and more friendly practices from takaful operators including its insurance agents. The main purpose of this paper is to identify the factors that influence the customers purchasing intention of Takaful Insurance offered by corporate insurance agent, Perbadanan Melaka Holdings Sdn. Bhd. This study focused on the working income group, insurance clients and people with no insurance coverage living in Melaka. Based on the output from questionnaire distributed to 300 respondents using convenience sampling and analysed using specific business tools and regression analysis, the result from this investigation indicated that customer knowledge, perception of customer and service quality were significantly correlated with customer purchasing intention of Takafu Insurance offered by Perbadanan Melaka Holdings Sdn. Bhd. The findings were seen consistent with the hypotheses formulated by previous study and can be applied to strengthen the Takaful Insurance in Malaysia.